Freedom of Expression and Democracy - Bhagwat, Ashutosh; Weinstein, James (The Oxford Handbook of Freedom of Speech, 2021)
This chapter focuses on the relationship between freedom of expression and democracy from both a historical and a theoretical perspective. The term ‘freedom of expression’ includes free speech, freedom of the press, the right to petition government, and freedom of political association. Eighteenth-century proponents of popular government had long offered democratic justifications for freedom of expression. The chapter then demonstrates that freedom of political expression is a necessary component of democracy. It describes two core functions of such expression: an informing and a legitimating one. Finally, the chapter examines the concept of ‘democracy’, noting various ways in which democracies vary among themselves, as well as the implications of those variations for freedom of expression. Even before democratic forms of government took root in the modern world.